Lithium secondary battery

JP7643800B2Active Publication Date: 2025-03-11LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023546125
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2022-10-04
Publication Date
2025-03-11
Estimated Expiration
2042-10-04

AI Technical Summary

Benefits of technology

【0018】 本発明のリチウム二次電池は、構造内にビニル基が置換されたイミダゾール系化合物と、リチウムジフルオロホスフェートとを添加剤として含む非水電解液、および特定組成の正極活物質を含む正極を併用することで、電解質の分解産物として発生するルイス酸(PF5)を効果的に除去(scavenging)するとともに、正極の表面で電気化学的に分解されて安定なイオン伝導性被膜を形成することで、高温安定性と、高温サイクル特性および異常な電圧降下現象が改善されたリチウム二次電池を実現することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643800000001
    Figure 0007643800000001
  • Figure 0007643800000002
    Figure 0007643800000002
  • Figure 0007643800000003
    Figure 0007643800000003
Patent Text Reader

Abstract

The present invention relates to a lithium secondary battery with an improved abnormal voltage drop phenomenon. The lithium secondary battery includes a negative electrode including a negative electrode active material, a positive electrode including a positive electrode active material represented by Chemical Formula 1, a separator interposed between the negative electrode and the positive electrode, and a non-aqueous electrolyte, and the non-aqueous electrolyte may include a lithium salt, a non-aqueous organic solvent, a compound represented by Chemical Formula 2 as a first additive, and lithium difluorophosphate as a second additive.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0133482 filed on October 7, 2021 and Korean Patent Application No. 10-2022-0125821 filed on September 30, 2022, and all contents disclosed in the documents of said Korean patent applications are incorporated by reference into this specification.

[0002] The present invention relates to a lithium secondary battery having improved battery durability. [Background technology]

[0003] In modern society, dependency on electrical energy is increasing more and more. Accordingly, research into new renewable energy sources that can increase the production of electrical energy without causing environmental problems is attracting attention.

[0004] On the other hand, new renewable energy sources have intermittent power generation characteristics, so large-capacity power storage devices are essential to ensure a stable supply of power. Among such power storage devices, lithium-ion batteries have been commercialized and are attracting attention as devices that exhibit high energy density.

[0005] A lithium-ion battery generally comprises a positive electrode including a positive electrode active material made of a transition metal oxide containing lithium, a negative electrode including a negative electrode active material capable of storing lithium ions, an electrolyte that serves as a medium for transmitting the lithium ions, and a separator.

[0006] The positive electrode stores energy through the oxidation-reduction reaction of a transition metal, which means that the transition metal must be an essential component of the positive electrode material.

[0007] The electrolyte is composed of a lithium salt, an organic solvent for dissolving the lithium salt, and functional additives. In order to improve the electrochemical properties of the battery, it is important to appropriately select these components.

[0008] On the other hand, lithium salts contained in non-aqueous electrolytes, typically LiPF6, are vulnerable to heat and moisture, and react with moisture in the cell or are thermally decomposed to generate Lewis acids such as HF and PF5. These Lewis acids corrode and deteriorate the passive film formed at the electrode-electrolyte interface. This induces a side reaction between the exposed surface of the positive electrode and the electrolyte, inducing the elution of transition metal ions from the positive electrode.

[0009] In particular, when a positive electrode active material using high-content nickel (High-Ni) with a Ni content of more than 0.5 is used, the deformation and collapse of the crystal structure of the positive electrode active material during repeated charge / discharge processes or exposure to high temperatures makes it more likely that transition metals will leach out of the positive electrode and the positive electrode structure will collapse. The leachable transition metals move to the negative electrode via the electrolyte and are then electrodeposited on the surface of the negative electrode, causing destruction of the SEI (Solid Electrolyte Interphase) film and additional consumption of lithium ions due to regeneration reactions, resulting in increased resistance, reduced capacity, and abnormal voltage drop. In addition, the decomposition of the electrolyte solvent is further promoted, accelerating gas generation, which causes problems such as deterioration of stability and high-temperature durability.

[0010] Therefore, in order to solve these problems, research is ongoing to develop a lithium secondary battery that combines a positive electrode containing a positive electrode active material of a specific composition with a non-aqueous electrolyte of a specific composition that can remove by-products (such as HF and PF5) generated by the thermal decomposition of lithium salts and form a stable coating on the surface of the electrode. Summary of the Invention [Problem to be solved by the invention]

[0011] In order to solve the above problems, an object of the present invention is to provide a lithium secondary battery having improved high-temperature stability, high-temperature cycle characteristics, and abnormal voltage drop phenomenon, by using a positive electrode containing a positive electrode active material of a specific composition in combination with a nonaqueous electrolyte solution containing two types of additives capable of forming a stable ion-conductive coating on the surface of the electrode. [Means for solving the problem]

[0012] In order to achieve the above object, in one embodiment of the present invention, a negative electrode including a negative electrode active material; A positive electrode including a positive electrode active material represented by the following chemical formula 1; a separator interposed between the negative electrode and the positive electrode; A non-aqueous electrolyte solution, The non-aqueous electrolyte solution includes a lithium salt, a non-aqueous organic solvent, A compound represented by the following chemical formula 2 as a first additive; A lithium secondary battery is provided, comprising: a second additive, lithium difluorophosphate;

[0013] [Chemical formula 1] Li a Ni x Co y M 1 z M 2 w O2

[0014] In the above Chemical Formula 1, M 1 is Mn, Al, or a combination thereof; M 2 is at least one selected from the group consisting of Al, Zr, W, Ti, M, Ca, and Sr; 0.8≦a≦1.2, 0.7≦x<1, 0 <y<0.3、0<z<0.3、0.01<w≦0.2である。

[0015] [ka]

[0016] In the above Chemical Formula 2, R is an alkylene group having 1 to 5 carbon atoms.

[0017] The weight ratio of the compound represented by Chemical Formula 2 and lithium difluorophosphate may be 1:2 to 1:15. Effect of the Invention

[0018] The lithium secondary battery of the present invention uses a non-aqueous electrolyte solution containing an imidazole compound having a vinyl group substituted in its structure and lithium difluorophosphate as additives, and a positive electrode containing a positive electrode active material of a specific composition, thereby effectively scavenging Lewis acid (PF5) generated as a decomposition product of the electrolyte and electrochemically decomposing the Lewis acid on the surface of the positive electrode to form a stable ion-conductive coating, thereby achieving a lithium secondary battery with improved high-temperature stability, high-temperature cycle characteristics, and abnormal voltage drop phenomenon. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention will now be described in more detail.

[0020] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0021] However, in this specification, the terms "including," "comprising," or "having" are intended to specify the presence of implemented features, numbers, steps, components, or combinations thereof, and should not be understood to preclude the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.

[0022] Prior to describing the present invention, in the description of "carbon number a to b" in the specification, "a" and "b" refer to the number of carbon atoms contained in a specific functional group. That is, the functional group may contain "a" to "b" carbon atoms. For example, "an alkyl group having 1 to 5 carbon atoms" refers to an alkyl group having 1 to 5 carbon atoms, i.e., -CH3, -CH2CH3, -CH2CH2CH3, -CH2(CH3)CH3, -CH(CH3)CH3, and -CH(CH3)CH2CH3.

[0023] In addition, in this specification, unless otherwise defined, "substituted" means that at least one hydrogen bonded to a carbon is replaced with an element other than hydrogen, for example, with an alkyl group having 1 to 5 carbon atoms or with fluorine.

[0024] Also, in this specification, "%" means % by weight, unless expressly indicated otherwise.

[0025] In general, transition metals are easily dissolved from the positive electrode into the electrolyte due to hydrogen fluoride (HF) generated from the electrolyte during battery operation or structural changes in the positive electrode due to repeated charging and discharging, which reduces the amount of available lithium ions in the battery and may cause deterioration of the battery capacity. In addition, the dissolved transition metal ions are not only re-deposited on the positive electrode, increasing the resistance of the positive electrode, but also migrate to the negative electrode through the electrolyte and destroy the solid electrolyte interphase (SEI) film, or are electrodeposited on the surface of the negative electrode and grow in a dendritic shape, causing an internal short circuit in the battery. If the decomposition reaction of the electrolyte is accelerated due to this series of reactions, the negative electrode interface resistance increases, causing self-discharge of the negative electrode, resulting in additional low voltage failure.

[0026] An object of the present invention is to provide a lithium secondary battery equipped with a nonaqueous electrolyte solution for lithium secondary batteries containing two types of additives that can remove transition metal ions that cause such deterioration and defective behavior, prevent them from being electrodeposited on the negative electrode, and form strong coatings on the surfaces of the positive and negative electrodes, thereby suppressing additional elution of the transition metals.

[0027] Lithium secondary battery Specifically, one embodiment of the present invention comprises: a negative electrode including a negative electrode active material; A positive electrode including a positive electrode active material represented by the following chemical formula 1; a separator interposed between the negative electrode and the positive electrode; A non-aqueous electrolyte solution, The non-aqueous electrolyte solution includes a lithium salt, a non-aqueous organic solvent, A compound represented by the following chemical formula 2 as a first additive; A lithium secondary battery is provided, comprising: a second additive, lithium difluorophosphate;

[0028] [Chemical formula 1] Li a Ni x Co y M 1 z M 2 w O2

[0029] In the above Chemical Formula 1, M 1 is Mn, Al, or a combination thereof; M 2 is at least one selected from the group consisting of Al, Zr, W, Ti, M, Ca, and Sr; 0.8≦a≦1.2, 0.7≦x<1, 0 <y<0.3、0<z<0.3、0.01<w≦0.2である。

[0030] [ka]

[0031] In the above Chemical Formula 2, R is an alkylene group having 1 to 5 carbon atoms.

[0032] The lithium secondary battery of the present invention may be manufactured by forming an electrode assembly in which a positive electrode, a negative electrode, and a separator are sequentially stacked between the positive electrode and the negative electrode, housing the electrode assembly in a battery case, and then introducing the nonaqueous electrolyte of the present invention into the battery case.

[0033] The method for manufacturing the lithium secondary battery of the present invention may be manufactured and applied by a conventional method known in the art, and will be described in detail below.

[0034] Each of the components constituting the lithium secondary battery of the present invention will be described in more detail below.

[0035] (1) Negative electrode The negative electrode of the present invention will now be described.

[0036] The negative electrode of the present invention includes a negative electrode active material layer containing a negative electrode active material, and the negative electrode active material layer may further include a conductive material and / or a binder, as necessary.

[0037] As the negative electrode active material, various negative electrode active materials used in the art, such as carbon-based negative electrode active materials, silicon-based negative electrode active materials, or mixtures thereof, may be used.

[0038] According to an embodiment, the negative electrode active material may include a carbon-based negative electrode active material, and the carbon-based negative electrode active material may be any of various carbon-based negative electrode active materials used in the art, such as graphite-based materials such as natural graphite, artificial graphite, and Kish graphite; pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes, soft carbon, hard carbon, etc. The shape of the carbon-based negative electrode active material is not particularly limited, and materials of various shapes such as amorphous, plate-like, flaky, spherical, or fibrous may be used.

[0039] Preferably, the negative electrode active material is at least one carbon-based negative electrode active material selected from natural graphite and artificial graphite. In order to increase the adhesive strength with the current collector and suppress detachment of the active material, both natural graphite and artificial graphite may be used.

[0040] According to another embodiment, the negative electrode active material may include a silicon-based negative electrode active material in addition to the carbon-based negative electrode active material.

[0041] The silicon-based negative electrode active material is, for example, metal silicon (Si), silicon oxide (SiO x, where 0 < x < 2), silicon carbide (SiC), and Si - Y alloy (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Si) may be included. The element Y may be selected from the group consisting of M, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db (dubnium), Cr, Mo, W, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0042] Since the silicon - based negative electrode active material exhibits higher capacity characteristics than the carbon - based negative electrode active material, when the silicon - based negative electrode active material is further included, even more excellent capacity characteristics can be obtained. However, a negative electrode containing a silicon - based negative electrode active material contains more oxygen - rich components in the SEI film compared to a graphite negative electrode, and an SEI film containing oxygen - rich components tends to be more easily decomposed when Lewis acids such as HF or PF5 are present in the electrolyte. Therefore, in order to maintain a stable SEI film, a negative electrode containing a silicon - based negative electrode active material needs to suppress the generation of Lewis acids such as HF and PF5 in the electrolyte or remove (or scavenge) the generated Lewis acids. The non - aqueous electrolyte according to the present invention forms stable coatings on the positive and negative electrodes and contains an electrolyte additive with excellent Lewis acid removal effect, so that the decomposition of the SEI film can be effectively suppressed when using a negative electrode containing a silicon - based active material.

[0043] On the other hand, the mixing ratio of the silicon - based negative electrode active material and the carbon - based negative electrode active material may be 3:97 to 99:1, preferably 5:95 to 15:85 by weight. When the mixing ratio of the silicon - based negative electrode active material and the carbon - based negative electrode active material satisfies the above range, the capacity characteristics are improved, the volume expansion of the silicon - based negative electrode active material is suppressed, and excellent cycle performance can be ensured.

[0044] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer. When the content of the negative electrode active material is in the above range, excellent capacity characteristics and electrochemical characteristics can be obtained.

[0045] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 1 to 20% by weight based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive powders such as carbon fluoride powder, aluminum powder, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0046] The binder is a component that assists the bonding between the conductive material, the active material, and the current collector, and is usually added in an amount of 1 to 30% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include fluororesin-based binders including polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber-based binders including styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, and styrene-isoprene rubber; cellulose-based binders including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyalcohol-based binders including polyvinyl alcohol; polyolefin-based binders including polyethylene and polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders.

[0047] Meanwhile, the negative electrode may be manufactured by a method for manufacturing a negative electrode known in the art. For example, the negative electrode may be manufactured by a method of forming a negative active material layer by coating a negative active material slurry prepared by dissolving or dispersing a negative active material, and optionally a binder and a conductive material in a solvent, on a negative current collector, rolling and drying the slurry, or by casting the negative active material layer on a separate support, peeling off the support, and laminating the resulting film on the negative current collector.

[0048] The negative electrode current collector generally has a thickness of 3 to 500 μm. Such a negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. may be used. In addition, as with the positive electrode current collector, the binding force of the negative electrode active material may be strengthened by forming fine irregularities on the surface, and it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0049] The solvent may include water or an organic solvent such as NMP or alcohol, and may be used in an amount that provides a suitable viscosity when the negative electrode active material and, optionally, a binder and a conductive material are contained therein. For example, the solvent may be contained so that the concentration of solids in the active material slurry containing the negative electrode active material and, optionally, a binder and a conductive material, is 50% by weight to 75% by weight, preferably 40% by weight to 70% by weight.

[0050] (2) Positive electrode Next, the positive electrode will be described.

[0051] The positive electrode according to the present invention includes a positive electrode active material layer containing a positive electrode active material, and the positive electrode active material layer may further include a conductive material and / or a binder, as necessary.

[0052] The positive electrode active material may include a lithium-nickel-cobalt-manganese-transition metal (M) oxide represented by the following Chemical Formula 1:

[0053] [Chemical formula 1] Li a Ni x Co y M 1 z M 2 w O2

[0054] In the above Chemical Formula 1, M 1 may be Mn, Al, or a combination thereof, and preferably may be Mn, or Mn and Al.

[0055] M 2 is at least one selected from the group consisting of Al, Zr, W, Ti, M, Ca, and Sr, and may be preferably one or more selected from the group consisting of Al, Zr, Y, M, and Ti, and more preferably Al.

[0056] The a represents the molar ratio of lithium in the lithium nickel-based oxide, and may be 0.8≦a≦1.2, specifically 0.85≦a≦1.15, or more specifically 0.9≦a≦1.05. When the lithium molar ratio satisfies the above range, the crystal structure of the lithium nickel-based oxide can be stably formed.

[0057] The x represents the molar ratio of nickel in all metals other than lithium in the lithium nickel-based oxide, and may be 0.7≦x<1, specifically 0.75≦x≦0.99, more specifically 0.8≦x≦0.95, and even more specifically 0.85≦x≦0.95. When the nickel molar ratio satisfies the above range, a high energy density is exhibited and a high capacity can be realized.

[0058] Said y represents the molar ratio of cobalt in all the metals excluding lithium in the lithium nickel-based oxide, where 0 < y < 0.3, preferably 0.001 < y < 0.3, specifically 0.01 < y < 0.25, more specifically 0.01 ≤ y < 0.20, and even more specifically 0.01 ≤ y < 0.15. When the molar ratio of cobalt satisfies the above range, good resistance characteristics and output characteristics can be realized.

[0059] Said z represents the molar ratio of element M in all the metals excluding lithium in the lithium nickel-based oxide 1 and 0.001 < z < 0.25, preferably 0.01 ≤ z < 0.20, more preferably 0.01 ≤ z < 0.20, and even more specifically 0.01 ≤ z < 0.15. When the molar ratio of element M 1 satisfies the above range, it has excellent structural stability of the positive electrode active material.

[0060] Said w represents the molar ratio of element M in all the metals excluding lithium in the lithium nickel-based oxide 2 and 0.01 < w ≤ 0.2, specifically 0.01 < w ≤ 0.1, and preferably 0.01 < w ≤ 0.05.

[0061] Specifically, in order to realize a high-capacity battery, said single-particle type positive electrode active material contains 80 mol% or more of Ni based on the total number of moles of transition metals, such as Li(Ni 0.8 Co 0.15 Al 0.05 )O2, Li(Ni 0.85 Mn 0.08 Co 0.05 Al 0.02 )O2, Li(Ni 0.86 Mn 0.07 Co 0.05 Al 0.02 )O2, Li(Ni 0.87 Mn 0.07 Co 0.04 Al 0.02 )O2, or may contain Li(Ni 0.90 Mn 0.03 Co 0.05 Al 0.02 )O2.

[0062] When a lithium transition metal oxide having a high content of nickel (High-Ni) in which the Ni content is more than 0.7 is used as the positive electrode active material, Li +1 Ion and Ni +2 Because the sizes of the ions are similar, Li +1 Ion and Ni +2 The cation mixing phenomenon occurs, in which the position of ions changes. That is, due to the change in the oxidation number of Ni contained in the positive electrode active material, nickel transition metals having d orbitals should have a regular octahedral structure when coordinated in a high temperature environment, but due to the external energy supply, the order of the energy levels changes, and due to a heterogeneity reaction in which the oxidation number changes, a distorted octahedron is formed, resulting in deformation and collapse of the crystal structure of the positive electrode active material. Furthermore, a side reaction between the positive electrode active material and the electrolyte during high-temperature storage causes further side reactions in which transition metals, especially nickel metal, are eluted from the positive electrode active material, which leads to the electrolyte depletion and the collapse of the structure of the positive electrode active material, resulting in a decline in the performance of the secondary battery.

[0063] In the present invention, such problems can be improved by using a positive electrode containing a high content of nickel transition metal oxide and a non-aqueous electrolyte containing a specific additive. That is, the non-aqueous electrolyte of the present invention forms a strong ion-conductive coating on the surface of the positive electrode, and Li +1 Ion and Ni +2 By suppressing the phenomenon of cation mixing of ions and effectively suppressing side reactions between the positive electrode and the electrolyte, metal elution, etc., the structural instability of the high-capacity electrode can be mitigated. Therefore, a sufficient amount of nickel transition metal can be secured to ensure the capacity of the lithium secondary battery, thereby increasing the energy density and improving the output characteristics.

[0064] Meanwhile, the positive electrode active material may be included in an amount of 80 wt% to 99 wt%, specifically 90 wt% to 99 wt%, based on the total content of the positive electrode active material layer. In this case, if the content of the positive electrode active material is 80 wt% or less, the energy density may be reduced, and the capacity may be reduced.

[0065] Meanwhile, the conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples thereof include carbon powders such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; graphite powders such as natural graphite, artificial graphite, and graphite with highly developed crystal structures; conductive fibers such as carbon fibers and metal fibers; conductive powders such as carbon fluoride powder, aluminum powder, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives. The conductive material is usually added in an amount of 1 to 30% by weight based on the total content of the positive electrode active material layer.

[0066] Meanwhile, the binder is a component that plays a role in improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector, and is usually added in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer. Examples of such binders include fluororesin-based binders including polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber-based binders including styrene butadiene rubber (SBR), acrylonitrile butadiene rubber, and styrene-isoprene rubber; cellulose-based binders including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyalcohol-based binders including polyvinyl alcohol; polyolefin-based binders including polyethylene and polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders.

[0067] The positive electrode of the present invention as described above may be manufactured by a method known in the art. For example, the positive electrode may be manufactured by a method of forming a positive electrode active material layer by coating a positive electrode slurry prepared by dissolving or dispersing a positive electrode active material, a binder, and / or a conductive material in a solvent on a positive electrode current collector, drying and rolling the resulting layer, or by casting the positive electrode active material layer on a separate support, peeling off the support, and laminating the resulting film on a positive electrode current collector.

[0068] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface has been surface-treated with carbon, nickel, titanium, silver, or the like may be used.

[0069] The solvent may contain an organic solvent such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount that provides a suitable viscosity when the positive electrode active material, and optionally a binder and a conductive material, etc. are contained. For example, the active material slurry containing the positive electrode active material, and optionally a binder and a conductive material may be contained so that the solid content concentration in the active material slurry is 10% by weight to 90% by weight, preferably 30% by weight to 80% by weight.

[0070] (3) Separator The separator included in the lithium secondary battery of the present invention may be a commonly used conventional porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, either alone or in a laminated state, or a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, or the like, but is not limited thereto.

[0071] (4) Non-aqueous electrolyte Next, the nonaqueous electrolyte of the present invention will be described.

[0072] The non-aqueous electrolyte of the present invention may include a lithium salt, a non-aqueous organic solvent, a compound represented by Chemical Formula 2 as a first additive, and lithium difluorophosphate as a second additive, and may optionally further include a third additive.

[0073] (4-1) Lithium salt First, the lithium salt will be described as follows.

[0074] The lithium salt may be any one that is commonly used in non-aqueous electrolytes for lithium secondary batteries, and may be any one of those having a cation such as Li + and as an anion, F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , B 10 Cl 10 - , AlCl4 - , AlO4 - , PF6 - , SO3F - , CF3SO3 - , CH3CO2 - , CF3CO2 -, AsF6 - , SbF6 - , CH3SO3 - , (CF3CF2SO2)2N - , (CF3SO2)2N - , (FSO2)2N - , (PO2F2) - , (FSO2)(POF2)N - , BF2C2O4 - , BC4O8 - , PF4C2O4 - , PF2C4O8 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , C4F9SO3 - , CF3CF2SO3 - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , CF3(CF2)7SO3 - , and SCN - may include at least one selected from the group consisting of:

[0075] Specifically, the lithium salt is LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10, LiAlCl4, LiAlO4, LiPF6, LiSO3F, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiN(SO2F)2(lithium bis(fluorosulfonyl)imide, LiFSI), LiN(SO2CF2CF3)2(lithium bis(pentafluoroethanesulfonyl)imide, LiBETI), and LiN(SO2CF3)2(lithium bis(trifluoromethanesulfonyl)imide, LiTFSI), and in addition to the above-mentioned lithium salts, lithium salts commonly used in electrolytes for lithium secondary batteries can be used without limitation. Specifically, the lithium salt may include LiPF6.

[0076] The lithium salt may be appropriately changed within a range that is normally usable, but in order to obtain an optimal effect of forming a corrosion prevention coating on the electrode surface, it may be contained in the electrolyte at a concentration of 0.8 M to 3.0 M, specifically, at a concentration of 1.0 M to 3.0 M. When the lithium salt is contained in the above concentration range, the viscosity of the nonaqueous electrolyte can be controlled to realize optimal impregnation, and the mobility of lithium ions can be improved, thereby obtaining an effect of improving the capacity characteristics and cycle characteristics of the lithium secondary battery.

[0077] (4-2) Nonaqueous organic solvent The non-aqueous organic solvent is described as follows.

[0078] As the non-aqueous organic solvent, various non-aqueous organic solvents commonly used in non-aqueous electrolytes can be used without limitation, and the type is not limited as long as it minimizes decomposition due to oxidation reaction during the charge / discharge process of the secondary battery and can exhibit desired properties together with additives.

[0079] Specifically, the non-aqueous organic solvent may include at least one of a high-viscosity cyclic carbonate compound having a high dielectric constant and easily dissociating a lithium salt, and a linear carbonate compound having a low viscosity and a low dielectric constant.

[0080] The cyclic carbonate compound may include at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, and vinylene carbonate, and may include ethylene carbonate.

[0081] The linear carbonate compound may include at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, and specifically may include ethyl methyl carbonate (EMC).

[0082] In the present invention, the cyclic carbonate compound and the linear carbonate compound may be mixed and used, and in this case, the mixing ratio of the cyclic carbonate compound and the linear carbonate compound may be 10:90 to 80:20 by volume, specifically 30:70 to 50:50 by volume. When the mixing ratio of the cyclic carbonate compound and the linear carbonate compound satisfies the above range, a nonaqueous electrolyte having a higher electrical conductivity can be produced.

[0083] Meanwhile, in the present invention, in order to improve the defects of the carbonate-based compound and to increase the stability at high temperatures and high voltage operation, a propionate compound may be further mixed as the non-aqueous organic solvent.

[0084] The propionate compound may include at least one selected from the group consisting of methyl propionate, ethyl propionate (EP), propyl propionate, and butyl propionate, and specifically may include at least one of ethyl propionate and propyl propionate.

[0085] Meanwhile, in the nonaqueous electrolyte, the other components other than the nonaqueous organic solvent, such as the lithium salt, the oligomer, and the optional additives, are all nonaqueous organic solvents unless otherwise specified.

[0086] (4-3) First additive The nonaqueous electrolyte for a lithium secondary battery of the present invention may contain a compound represented by the following chemical formula 2 as a first additive.

[0087] [ka]

[0088] In the above Chemical Formula 2, R is an alkylene group having 1 to 5 carbon atoms.

[0089] The R may further include at least one unsaturated bond.

[0090] The compound represented by Chemical Formula 2 includes an imidazole structure that can act as a Lewis base. Therefore, the nitrogen atom of the imidazole group can effectively scavenge Lewis acids generated as decomposition products of lithium salts. In addition, the vinyl group included in the structure of the compound represented by Chemical Formula 2 can be reduced on the surface of the negative electrode when a certain voltage is reached during charging and discharging, and an ion-conductive coating can be formed on the surface of the negative electrode, thereby suppressing additional decomposition reactions of the electrolyte. Furthermore, even when charging and discharging are repeated or during high-temperature storage, the absorption and release of lithium ions from the negative electrode can be facilitated, improving cycle life characteristics and high-temperature storage performance, and effectively preventing electrodeposition of lithium ions due to dissolved transition metals or overvoltage, thereby improving the resistance increase rate.

[0091] Specifically, in the above chemical formula 2, R may be an alkylene group having 1 to 3 carbon atoms.

[0092] More specifically, the compound represented by Chemical Formula 2 may be a compound represented by Chemical Formula 2a below.

[0093] [ka]

[0094] The compound represented by Chemical Formula 2 may be included in an amount of 0.1 wt % to 5 wt % based on the total weight of the nonaqueous electrolyte.

[0095] When the compound represented by the formula 2 is contained within the above range, a secondary battery with improved performance can be manufactured. For example, when the content of the first additive is 0.1 wt % or more, a stabilizing effect and an elution suppressing effect can be obtained during the formation of the SEI film within a range that minimizes an increase in resistance, and an effect of improving abnormal voltage buildup can be obtained. In addition, when the content of the additive is 5 wt % or less, an increase in the viscosity of the electrolyte due to excess compounds can be prevented, and an increase in the battery resistance can be effectively prevented by suppressing the formation of an excessive coating, so that a maximum elution suppressing effect can be obtained within a range of an acceptable increase in resistance.

[0096] Specifically, the compound represented by Chemical Formula 2 is included in an amount of 0.3 wt % to 3 wt %, specifically 0.3 wt % to 2.5 wt %, based on the total weight of the nonaqueous electrolyte solution, in which case a secondary battery with improved performance can be manufactured.

[0097] (4-4) Second additive In addition, the nonaqueous electrolyte of the present invention can form a coating film containing an inorganic component and having improved thermal stability on the surface of the positive electrode by mixing an additive in the form of a lithium salt, such as lithium difluorophosphate (LiDFP), as the second additive.

[0098] The lithium difluorophosphate is a component for improving the long-term life characteristics of a secondary battery. It is electrochemically decomposed on the surfaces of the positive and negative electrodes to help form an ion-conductive film, thereby suppressing the elution of metal from the positive electrode and preventing side reactions between the electrodes and the electrolyte, thereby improving the high-temperature storage characteristics and cycle life characteristics of the secondary battery.

[0099] Meanwhile, in the nonaqueous electrolyte of the present invention, the weight ratio of the compound represented by Chemical Formula 2 as the first additive to the lithium difluorophosphate as the second additive may be 1:2 to 1:15. When the compound represented by Chemical Formula 2 and lithium difluorophosphate are contained in the above range, a coating having excellent thermal stability is formed on the surface of the electrode, and the effect of removing decomposition products generated from the lithium salt is further improved, thereby improving the output of the secondary battery.

[0100] Specifically, the compound represented by Formula 2 and lithium difluorophosphate may be included in a weight ratio of 1:2 to 1:10, more specifically, in a weight ratio of 1:2 to 1:7.

[0101] On the other hand, when the compound represented by Chemical Formula 2 and lithium difluorophosphate are contained at the same level of content, for example, when they are contained at a ratio of 1:1, the component with high ion conductivity generated by decomposition of difluorophosphate is relatively reduced, and the organic coating derived from the compound represented by Chemical Formula 2 is relatively thickly formed, which may increase the initial coating resistance and cause severe overpotential. Therefore, when used together with a positive electrode active material using a lithium transition metal oxide with a high content of nickel having an Ni content of more than 0.7, the decomposition of the electrolyte may be promoted, the deterioration rate of the active material may be accelerated, and the long-term durability (cycle characteristics, etc.) may be relatively decreased.

[0102] (4-5) Third additive In addition, the nonaqueous electrolyte for a lithium secondary battery of the present invention may further contain a third additive, if necessary, in addition to the two additives, in order to prevent the nonaqueous electrolyte from being decomposed in a high-output environment, which would cause the collapse of the negative electrode, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, overcharge prevention, and the effect of suppressing battery expansion at high temperatures.

[0103] Examples of such third additives include at least one selected from the group consisting of cyclic carbonate compounds, halogen-substituted carbonate compounds, sultone compounds, sulfate compounds, phosphate or phosphite compounds, borate compounds, benzene compounds, amine compounds, imidazole compounds, silane compounds, and lithium salt compounds.

[0104] Examples of the cyclic carbonate compounds include vinylene carbonate (VC) and vinyl ethylene carbonate (VEC).

[0105] The halogen-substituted carbonate compounds include fluoroethylene carbonate (FEC).

[0106] The sultone compound may be, for example, at least one compound selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethene sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone.

[0107] The sulfate compound may be, for example, ethylene sulfate (Esa), trimethylene sulfate (TMS), methyl trimethylene sulfate (MTMS), or the like.

[0108] The phosphate or phosphite compound may be, for example, one or more compounds selected from the group consisting of lithium difluoro(bisoxalato)phosphate, lithium difluorophosphate, lithium tetrafluorooxalatophosphate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(2,2,2-trifluoroethyl)phosphate, and tris(trifluoroethyl)phosphite.

[0109] Examples of the borate-based compound include tetraphenylborate, lithium oxalyldifluoroborate (LiODFB) capable of forming a coating on the surface of the negative electrode, and lithium bisoxalatoborate (LiB(C2O4)2, LiBOB).

[0110] The benzene-based compound may be fluorobenzene, and the amine-based compound may be triethanolamine or ethylenediamine.

[0111] Examples of the imidazole-based compound include lithium 2-trifluoromethyl-4,5-dicyanoimidazole, 1-methyl,5-propargyl imidazole, propargyl 1H-imidazole-1-carboxylate, 1-vinyl imidazole, and allyl 1H-imidazole-1-carboxylate.

[0112] The silane-based compound may be tetravinylsilane or the like.

[0113] The lithium salt compound is a compound different from the lithium salt contained in the nonaqueous electrolyte, and examples of the lithium salt include LiPO2F2, LiSO3F, and LiBF4.

[0114] Among such third additives, in order to form a stronger SEI coating on the surface of the negative electrode during the initial activation step, other additives having excellent coating formation effect on the surface of the negative electrode, specifically at least one selected from the group consisting of vinylene carbonate, 1,3-propane sultone, ethylene sulfate, fluoroethylene carbonate (FEC), LiBF4, and lithium difluorophosphate (LiPO2F2), may be included.

[0115] The third additive may be a mixture of two or more compounds, and may be included in an amount of 0.01 to 50 wt%, specifically 0.01 to 20 wt%, and preferably 0.05 to 15 wt%, based on the total weight of the non-aqueous electrolyte. When the content of the other additives is within the above range, high-temperature storage and cycle characteristics are improved, side reactions in the battery caused by the addition of an excessive amount are prevented, and the remaining or precipitation of unreacted substances is prevented, which is preferable.

[0116] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.

[0117] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention can be modified into various other forms, and the scope of the present invention should not be interpreted as being limited to the examples described below. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.

[0118] Working Example Example 1 (Production of non-aqueous electrolyte) LiPF6 was dissolved to a concentration of 1.0M in a non-aqueous organic solvent prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 30:70, and then 0.1 wt % of the compound represented by Formula 2a and 1.0 wt % of lithium difluorophosphate were added thereto, and 0.5 wt % of vinylene carbonate (VC), 0.5 wt % of 1,3-propane sultone (PS), and 1.0 wt % of ethylene sulfate (ESa) were added as a third additive to prepare a non-aqueous electrolyte (see Table 1 below).

[0119] (Secondary battery manufacturing) Cathode active material (Li(Ni) 0.85 Mn 0.08 Co 0.05 Al 0.02A cathode slurry (solid content: 72 wt%) was prepared by adding 1,2-dichloroethane (1,2,3-tetrafluoroethylene) (O2), conductive material (carbon black), and binder (polyvinylidene fluoride) in a weight ratio of 97.6:0.8:1.6 to a solvent, N-methyl-2-pyrrolidone (NMP). The cathode slurry was applied to a 13.5 μm-thick aluminum (Al) thin film, which was a cathode current collector, and dried, followed by roll pressing to prepare a cathode.

[0120] Anode active material (artificial graphite and natural graphite = 80:20 weight ratio), binder (SBR-CMC), and conductive material (carbon black) were added to the solvent water in a weight ratio of 95.6:3.4:1.0 to prepare anode slurry (solid content: 50 wt%). The anode slurry was applied to a copper (Cu) thin film as an anode current collector with a thickness of 6 μm, dried, and then roll pressed to prepare anode.

[0121] The positive electrode, a polyolefin-based porous separator coated with inorganic particles (Al2O3), and a negative electrode were sequentially stacked to prepare an electrode assembly, which was then placed in a pouch-shaped battery case and the non-aqueous electrolyte for lithium secondary batteries was injected to prepare a pouch-shaped lithium secondary battery having a driving voltage of 4.2 V or more.

[0122] Example 2. (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and then 0.1 wt % of the compound represented by Formula 2a and 0.8 wt % of lithium difluorophosphate were added thereto, and 0.5 wt % of vinylene carbonate (VC), 0.5 wt % of 1,3-propane sultone (PS), and 1.0 wt % of ethylene sulfate (ESa) were added as a third additive to prepare a non-aqueous electrolyte.

[0123] (Secondary battery manufacturing) A lithium secondary battery was produced in the same manner as in Example 1, except that the nonaqueous electrolyte prepared above was injected instead of the nonaqueous electrolyte prepared in Example 1.

[0124] Example 3. (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and then 0.3 wt % of the compound represented by Formula 2a and 1.0 wt % of lithium difluorophosphate were added thereto, and 0.5 wt % of vinylene carbonate (VC), 0.5 wt % of 1,3-propane sultone (PS), and 1.0 wt % of ethylene sulfate (ESa) were added as a third additive to prepare a non-aqueous electrolyte.

[0125] (Secondary battery manufacturing) A lithium secondary battery was produced in the same manner as in Example 1, except that the nonaqueous electrolyte prepared above was injected instead of the nonaqueous electrolyte prepared in Example 1.

[0126] Example 4. (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and then 0.3 wt % of the compound represented by Formula 2a and 0.8 wt % of lithium difluorophosphate were added thereto, and 0.5 wt % of vinylene carbonate (VC), 0.5 wt % of 1,3-propane sultone (PS), and 1.0 wt % of ethylene sulfate (ESa) were added as a third additive to prepare a non-aqueous electrolyte.

[0127] (Secondary battery manufacturing) A lithium secondary battery was produced in the same manner as in Example 1, except that the nonaqueous electrolyte prepared above was injected instead of the nonaqueous electrolyte prepared in Example 1.

[0128] Example 5. (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and then 0.5 wt % of the compound represented by Formula 2a and 1.0 wt % of lithium difluorophosphate were added thereto, and 0.5 wt % of vinylene carbonate (VC), 0.5 wt % of 1,3-propane sultone (PS), and 1.0 wt % of ethylene sulfate (ESa) were added as a third additive to prepare a non-aqueous electrolyte.

[0129] (Secondary battery manufacturing) A lithium secondary battery was produced in the same manner as in Example 1, except that the nonaqueous electrolyte prepared above was injected instead of the nonaqueous electrolyte prepared in Example 1.

[0130] Example 6. (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and then 0.5 wt % of the compound represented by Formula 2a and 0.5 wt % of lithium difluorophosphate were added thereto, and 0.5 wt % of vinylene carbonate (VC), 0.5 wt % of 1,3-propane sultone (PS), and 1.0 wt % of ethylene sulfate (ESa) were added as a third additive to prepare a non-aqueous electrolyte.

[0131] (Secondary battery manufacturing) A lithium secondary battery was produced in the same manner as in Example 1, except that the nonaqueous electrolyte prepared above was injected instead of the nonaqueous electrolyte prepared in Example 1.

[0132] Comparative Example 1 (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and 0.5 wt % vinylene carbonate (VC), 0.5 wt % 1,3-propane sultone (PS), and 1.0 wt % ethylene sulfate (ESa) were added to prepare a non-aqueous electrolyte.

[0133] (Secondary battery manufacturing) A lithium secondary battery was produced in the same manner as in Example 1, except that the nonaqueous electrolyte prepared above was injected instead of the nonaqueous electrolyte prepared in Example 1.

[0134] Comparative Example 2 (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and then 1.0 wt% of lithium difluorophosphate was added, followed by the addition of 0.5 wt% of vinylene carbonate (VC), 0.5 wt% of 1,3-propane sultone (PS), and 1.0 wt% of ethylene sulfate (ESa) to prepare a non-aqueous electrolyte.

[0135] (Secondary battery manufacturing) A lithium secondary battery was produced in the same manner as in Example 1, except that the nonaqueous electrolyte prepared above was injected instead of the nonaqueous electrolyte prepared in Example 1.

[0136] Comparative Example 3. (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and then 0.5 wt % of the compound represented by Formula 2a was added thereto, followed by the addition of 0.5 wt % of vinylene carbonate (VC), 0.5 wt % of 1,3-propane sultone (PS), and 1.0 wt % of ethylene sulfate (ESa) to prepare a non-aqueous electrolyte.

[0137] (Secondary battery manufacturing) A lithium secondary battery was produced in the same manner as in Example 1, except that the nonaqueous electrolyte prepared above was injected instead of the nonaqueous electrolyte prepared in Example 1.

[0138] Comparative Example 4. (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent to a concentration of 1.0 M, and then 0.5 wt % of a compound represented by the following formula 3 and 1.0 wt % of lithium difluorophosphate were added thereto, and 0.5 wt % of vinylene carbonate (VC), 0.5 wt % of 1,3-propane sultone (PS), and 1.0 wt % of ethylene sulfate (ESa) were added as a third additive to prepare a non-aqueous electrolyte.

[0139] [ka]

[0140] (Secondary battery manufacturing) A lithium secondary battery was produced in the same manner as in Example 5, except that the nonaqueous electrolyte prepared above was injected instead of the nonaqueous electrolyte prepared in Example 1.

[0141] Comparative Example 5. As the positive electrode active material, Li(Ni 0.85 Mn 0.08 Co 0.05 Al 0.02 )O2 instead of Li(Ni 0.8 Mn 0.1 Co 0.1 A lithium secondary battery was manufactured in the same manner as in Example 2, except that a positive electrode was manufactured using NCM1.

[0142] Comparative Example 6. As the positive electrode active material, Li(Ni 0.85 Mn 0.08 Co 0.05 Al 0.02 )O2 instead of Li(Ni 0.8 Mn 0.1 Co 0.1 A lithium secondary battery was manufactured in the same manner as in Example 4, except that a positive electrode was manufactured using 1,2-dichloro-1,2-trifluoroethylene (NCM1).

[0143] Comparative Example 7. As the positive electrode active material, Li(Ni 0.85 Mn 0.08 Co0.05 Al 0.02 )O2 instead of Li(Ni 0.6 Mn 0.2 Co 0.2 A lithium secondary battery was manufactured in the same manner as in Example 3, except that a positive electrode was manufactured using NCM2.

[0144] Comparative Example 8. As the positive electrode active material, Li(Ni 0.85 Mn 0.08 Co 0.05 Al 0.02 )O2 instead of Li(Ni 0.6 Mn 0.2 Co 0.2 A lithium secondary battery was manufactured in the same manner as in Example 5, except that a positive electrode was manufactured using NCM2.

[0145] [Table 1]

[0146] Meanwhile, in Table 1, the abbreviations of the compounds have the following meanings. NCMA:Li(Ni 0.85 Mn 0.08 Co 0.05 Al 0.02 )O2 NCM1:Li(Ni 0.8 Mn 0.1 Co 0.1 )O2 NCM2:Li(Ni 0.6 Mn 0.2 Co 0.2 )O2

[0147] Experimental Example Experimental Example 1: Evaluation of the resistance increase rate after high-temperature storage Each of the lithium secondary batteries manufactured in Examples 1 to 6 and the lithium secondary batteries manufactured in Comparative Examples 1 to 8 was charged at 25° C. under constant current / constant voltage conditions at a rate of 0.33 C to 4.2 V, and then discharged at a constant current condition at a rate of 0.33 C to 2.5 V (one cycle) for three cycles. After that, the batteries were discharged at a rate of 2.5 C at SOC 50% for 10 seconds, and the voltage drop value observed when the battery was discharged was measured, and the initial resistance value was calculated according to the following formula 1.

[0148] Thereafter, the lithium secondary batteries manufactured in Examples 1 to 6 and the lithium secondary batteries manufactured in Comparative Examples 1 to 8 were stored at 60° C. and SOC 100% for 3 weeks, cooled to 25° C., and discharged at 2.5C rate and SOC 50% for 10 seconds. The voltage drop was measured and the resistance increase rate (%) was calculated according to the following formula 2. The results are shown in Table 2 below.

[0149] [Formula 1] Initial discharge resistance (ohm) = (voltage before discharge - voltage after discharge) [V] / discharge current value [A]

[0150] [Formula 2] Resistance increase rate (%) = {(resistance after high temperature storage - resistance before high temperature storage) / resistance before high temperature storage} x 100

[0151] [Table 2]

[0152] Referring to Table 2, it can be seen that the secondary batteries of Examples 1 to 5 have a significantly reduced resistance increase rate (%) after high-temperature storage compared to the lithium secondary batteries of Comparative Examples 1 to 4 using a nonaqueous electrolyte solution not containing the first additive and / or the second additive, and the lithium secondary batteries of Comparative Examples 5 to 8 having positive electrodes with different compositions of positive electrode active materials.

[0153] On the other hand, the secondary battery of Example 6, which has a non-aqueous electrolyte containing equal amounts of the first additive and the second additive, shows a relatively increased resistance increase rate (%) after high-temperature storage as compared to the secondary batteries of Examples 1 to 5, as the initial film resistance increases.

[0154] Experimental Example 2. Evaluation of initial discharge capacity and discharge capacity retention rate (%) The lithium secondary batteries produced in Examples 1 to 6 and the lithium secondary batteries produced in Comparative Examples 1 to 4, 7, and 8 were each charged at 25° C. under constant current / constant voltage conditions at a rate of 0.33 C to 4.2 V, and then discharged at a rate of 0.33 C to 2.5 V under constant current conditions (one cycle) for three cycles. After that, the initial discharge capacity was measured, and the results are shown in Table 3 below.

[0155] Thereafter, the lithium secondary batteries manufactured in Examples 1 to 6 and the lithium secondary batteries manufactured in Comparative Examples 1 to 4, 7, and 8 were each stored at 60° C. and SOC 100% for 3 weeks, and then cooled to 25° C., after which the discharge capacity was measured and the discharge capacity retention rate (%) was calculated according to the following formula 3. The results are shown in Table 3 below.

[0156] [Formula 3] Discharge capacity retention rate (%) = (discharge capacity after high-temperature storage at 60°C for 3 weeks / initial discharge capacity) x 100

[0157] [Table 3]

[0158] Referring to Table 3, it can be seen that the secondary batteries of Examples 1 to 6 have increased initial discharge capacities compared to Comparative Examples 2 to 4, 7, and 8.

[0159] On the other hand, the secondary battery of Comparative Example 1, which has a nonaqueous electrolyte solution that does not contain the first additive and the second additive, cannot form a stable coating, unlike the secondary batteries of the Examples in which Li ions are easily consumed and sufficient coating can be formed. Therefore, the amount of Li ions consumed during the initial performance evaluation is small, and it can be seen that the initial discharge capacity is relatively increased compared to the secondary batteries of Examples 1 to 6.

[0160] Furthermore, referring to Table 3, it can be seen that the secondary batteries of Examples 1 to 5 have increased discharge capacity retention rates (%) compared to Comparative Examples 1 to 4, 7, and 8.

[0161] On the other hand, it can be seen that the secondary battery of Example 6, which has a nonaqueous electrolyte containing equal amounts of the first additive and the second additive, has a relatively decreased discharge capacity retention rate (%) after high-temperature storage compared to the secondary batteries of Examples 2 to 6 due to an increase in the coating resistance.

[0162] Experimental Example 3: Evaluation of volume increase rate after high temperature storage The lithium secondary batteries prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were each charged to 4.2 V under a constant current / constant voltage (0.05 C cut) condition of 0.33 C C-rate at room temperature (25° C.), and then insulated with imide tape and the initial volume was measured. The volume was calculated by measuring the weight inside and outside of the triple distilled water based on Archimedes' principle.

[0163] Then, after storing at 60° C. for 3 weeks, the thickness change of each lithium secondary battery after high-temperature storage was measured, and the measurement results were substituted into the following Equation 4 to calculate the volume change rate. The results are shown in Table 4 below.

[0164] [Formula 4] Volume increase rate (%) = {(volume after high-temperature storage - volume before high-temperature storage) / volume before high-temperature storage}} x 100

[0165] [Table 4]

[0166] Referring to Table 4, the secondary batteries of Examples 1 to 6 of the present invention had a volume increase rate (%) of about 3.6% or less after storage at 60° C. for 3 weeks, which shows an improvement in the volume increase rate (%) after high temperature storage compared to the secondary batteries of Comparative Examples 1 to 4.

Claims

1. a negative electrode including a negative electrode active material; A positive electrode including a positive electrode active material represented by the following chemical formula 1; a separator interposed between the negative electrode and the positive electrode; A non-aqueous electrolyte solution, The non-aqueous electrolyte solution includes a lithium salt, a non-aqueous organic solvent, A compound represented by the following chemical formula 2 as a first additive; and lithium difluorophosphate as a second additive, The weight ratio of the compound represented by Formula 2 to the lithium difluorophosphate is 1:2 to 1:7; The compound represented by Chemical Formula 2 is contained in an amount of 0.3 wt % to 5 wt % based on the total weight of the non-aqueous electrolyte. [Chemical formula 1] Li a Ni x Co y M 1 z M 2 w O 2 (In the above Chemical Formula 1, M 1 is Mn, Al, or a combination thereof; M 2 is at least one selected from the group consisting of Al, Zr, W, Ti, Ca, and Sr; 0.8≦a≦1.2, 0.7≦x<1, 0<y<0.3, 0<z<0.3, 0.01<w≦0.2.) 【Chemistry 1】 (In the above Chemical Formula 2, R is an alkylene group having 1 to 5 carbon atoms.

2. In the above Chemical Formula 1, M 2 is one or more selected from the group consisting of Al, Zr, and Ti, and 0.85≦a≦1.15, 0.75≦x≦0.99, 0.001<y<0.3, 0.001<z<0.25, and 0.01<w≦0.

1.

3. In the above Chemical Formula 1, M 2 The lithium secondary battery according to claim 1 , wherein a is Al, 0.9≦a≦1.05, 0.8≦x≦0.95, 0.01<y<0.25, 0.01≦z<0.20, and 0.01<w≦0.

05.

4. The positive electrode active material is Li(Ni 0.8 Co 0.15 A 0.05 ) O 2 , Li(Ni 0.85 Mn 0.08 Co 0.05 A 0.02 ) O 2 , Li(Ni 0.86 Mn 0.07 Co 0.05 A 0.02 ) O 2 , Li(Ni 0.87 Mn 0.07 Co 0.04 A 0.02 ) O 2 , or Li(Ni 0.90 Mn 0.03 Co 0.05 A 0.02 ) O 2 The lithium secondary battery according to claim 1 ,

5. 2. The lithium secondary battery according to claim 1, wherein in Chemical Formula 2, R is an alkylene group having 1 to 3 carbon atoms.

6. The lithium secondary battery of claim 1 , wherein the compound represented by Chemical Formula 2 is a compound represented by Chemical Formula 2a: 【Chemistry 2】

7. 2. The lithium secondary battery of claim 1, wherein the compound represented by Formula 2 is contained in an amount of 0.5 wt % to 5 wt % based on the total weight of the non-aqueous electrolyte.

8. The nonaqueous electrolyte solution is The solvent contains at least one organic solvent selected from the group consisting of a cyclic carbonate organic solvent, a linear carbonate organic solvent, and a linear ester organic solvent; 2. The lithium secondary battery according to claim 1, further comprising at least one third additive selected from the group consisting of cyclic carbonate compounds, halogen-substituted carbonate compounds, sultone compounds, sulfate compounds, phosphate or phosphite compounds, borate compounds, benzene compounds, amine compounds, imidazole compounds, silane compounds, and lithium salt compounds.

Citation Information

Patent Citations

  • Lithium ion battery electrolyte, lithium ion battery and application

    CN110707360A

  • Lithium ion secondary battery

    JP2019160615A